Contact allergy to allergens in the swedish baseline series overrepresented in Diabetes patients with skin reactions to medical devices - a retrospective study from southern Sweden - Ulriksdotter, Josefin; Sukakul, Thanisorn; Bruze, Magnus; Mowitz, Martin; Ofenloch, Robert; Svedman, Cecilia (Acta dermato-venereologica, 2024)
Allergic contact dermatitis is reported among individuals using continuous glucose monitoring systems and insulin pumps. The aim of this study was to describe contact allergy patterns for allergens in the Swedish baseline series and medical device-related allergens among users. Contact allergy to baseline series allergens and isobornyl acrylate was compared between diabetes patients and dermatitis patients patch-tested at the Department of Occupational and Environmental Dermatology during 2017 to 2020. Fifty- four diabetes patients and 2,567 dermatitis patients were included. The prevalence of contact allergy to fragrance mix II and sesquiterpene lactone mix was significantly higher in diabetes patients compared with dermatitis patients. Of the diabetes patients 13.0% and of the dermatitis patients 0.5% tested positive to sesquiterpene lactone mix (p < 0.001). Of the diabetes patients 7.4% and of the dermatitis patients 2.3% tested positive to fragrance mix II (p = 0.041). Of the diabetes patients 70.4% tested positive to medical device-related allergens. Of the diabetes patients 63.0% and of the dermatitis patients 0.2% were allergic to isobornyl acrylate (p < 0.001). In conclusion, not only medical device-related contact allergies, but also contact allergy to baseline series allergens (fragrance mix II and sesquiterpene lactone mix), is overrepresented in diabetes patients who use medical devices.
Gesehen am 20.12.2024